Harmonisasi Pengaturan Pengalihan Objek Jaminan Fidusia dalam Perspektif Hukum Positif dan Hukum Islam Berbasis Rahn Tasjily - Dea Dahlia; Risna Menda Lovinta Siregar; Sarah Alzagladi; Muhammad Abdul Zalil (Jurnal Hukum Lex Generalis, 2026)
This research is motivated by the high prevalence of debtors transferring fiduciary security objects without the creditor's consent, which potentially results in legal losses for the creditor. This study aims to analyze the differences and alignment of regulations regarding the transfer of fiduciary security objects in positive law and Islamic law, specifically through the concept of rahn tasjily. The method employed is normative legal research with conceptual and comparative law approaches. The results indicate that in positive law, the transfer of fiduciary security objects is restricted and requires written consent from the creditor. Meanwhile, in Islamic law, through the rahn tasjily concept, such transfer is permissible while remaining grounded in the principles of prudence, justice, and the protection of all parties. The novelty of this research lies in the construction of a normative harmonization between positive law and Islamic law to strengthen creditor protection within a dual legal system.